Capital structure, stock exchanges in Chile: 2007 to 2016 - Marcelo Rabelo Henrique; Sandro Braz Silva; Antonio Saporito (Journal of Economics, Finance and Administrative Science, 2021)
Purpose - The article consists of analyzing the behavior of the determinants of the capital structure of Chilean companies between 2007 and 2016. The objective of this study was achieved through a typology of research based on bibliographic, documentary, exploratory and explanatory, considering annual financial reports from Economática in the chosen period. Design/methodology/approach - As this is a research study with a quantitative approach, the statistical tools used were descriptive analysis, Pearson correlation, variance inflation factor (VIF) and panel regression. Findings - The results show that Chilean companies (240) have higher and costly long-term debt. These companies have high averages in current liquidity, return to shareholders, growth in sales and assets and market-to-book (MTB). Long-term debt was highlighted with an explanatory power of 85%. Current liquidity was highlighted as being significant in most of the indebtedness proposed in the survey, failing to register brands like this in expensive short-term and long-term indebtedness. It is noticed that flip flops companies are more prone to the pecking order theory (POT). The gap occupied by this study is linked to research involving South American countries, especially the Chilean market, and the determinants of the capital structure. Originality/value - As future research, it is suggested to include other types of variables related to indebtedness and the same action for its determinants, in addition to the speed technique of adjusting corporate debts.
Keywords: 330; Analysis of multiple linear regression; Debt; Determinants of the capital structure; Pecking order theory; Trade-off theory